(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Kampung chicken is Indonesian native chicken that potential to be developed as commercial chicken. The large-scale breeders less interest to breed kampung chicken because it has slow growth to reach slaughter weight than commercial meat type. Therefore, kampung chicken’s performance need to be improved by crossing with commercial meat type that has fast growth. This research purposed to observed the effect performance of first generation (F1) from commercial meat type crossing with kampung and their reciprocal. Research conducted performance of crossing chicken in age 0-12 weeks age. T test used for knowing difference body weight mean, body weight gain, feed consumption, and feed convertion rate. The result of this research were not significant between KB cock with BK cock and KB hen with BK hen on body weight, body weight gain, feed consumption, and feed convertion rate. Whereas mortality percentage BK chicken was higher than KB chicken althought less of mortality. KB and BK cocks had better performance than hens. Reciprocal crossing between kampung chicken and commercial meat type had performance better than kampung chicken, so crossing had been increased genetic quality of kampung chicken.